Does an intervention focused on discussing problem solving show potential for improving individual learning outcomes? - Dlamini, Mthokoziseni Sonnyboy (My University, 2017)
Attainment in problem solving in mathematics is one of the cognitive levels that is used to guide the assessments in South Africa. Unfortunately, it is one of the levels in which most students do not perform well. This research investigates whether the approach taken in an intervention focused on discussing problem solving shows potential for improving individual learning outcomes? A pre-test and post-test on problem solving questions was administered to two Grade 8 classes from a private school in a Northern suburb of Johannesburg. The intervention 1 class wrote a pre-test and thereafter the class was taught how to deal with mathematical problems and later the class wrote a post-test. The intervention 2 class only wrote the pre-test and the post-test, with the usual kind of teaching. Not only did the intervention 1 class average improve by 10% from 38% on the pre-test to 48% on the post-test but also the class improved in terms of using models to solve problems. On the other hand, the intervention 2 class improved by 14% from 24% to 38%. However, while the intervention 2 class had an improvement in terms of using models to solve problems, the improvement was not substantial. The results also show that mathematical problem solving involving ratios remain a challenge for the grade 8 students in my school and that more work needs to be done to ensure success in mathematical problems involving ratios. Keywords: Problem-solving; intervention 2 class; intervention 1 class, cognitive levels
A research report submitted to the Faculty of Science, in partial fulfilment of the requirements for the degree of Master of Science, University of the Witwatersrand. Johannesburg, 22 August 2017.
Keywords: Mathematics--Study and teaching--South Africa; Educational attainment--South Africa; Problem solving--Problems, exercises, etc.; Learning--Evaluation